Association of Immune Cell Subsets With Longevity: The Cardiovascular Health Study. - Dobrota Lai, Sylvie; Bůzková, Petra; Delaney, Joseph A; Olson, Nels C; Psaty, Bruce M; Huber, Sally A; Doyle, Margaret F; Tracy, Russell P; Odden, Michelle C (J Gerontol A Biol Sci Med Sci, 2025)
BACKGROUND: Changes in the immune system are a potential biological mechanism of aging. We investigated the association of circulating immune cell subsets with age at death and survival to age 90. METHODS: Immune cell phenotypes were measured at baseline in 1 625 adults, aged 70-85 years, in the Cardiovascular Health Study. We selected 5 primary immune cell subsets: gamma-delta T-cells, natural killer cells, CD8+ T effector memory CD45RA expressing cells(TEMRA) cells, ratio of CD4+ to CD8+ cells, and ratio of naïve to memory CD8+ cells. We used linear regression and Poisson models, adjusting for demographics and clinical factors; and tested for effect modification by sex and race. In a secondary analysis, we investigated 23 additional immune cell subsets, using the Holm-Bonferroni method to adjust for multiple comparisons. RESULTS: No primary immune cell subsets were significantly associated with longevity. Two secondary subsets were significantly associated with age at death. Each SD higher proportion of CD4+CD57+ cells was associated with a 0.64-year earlier death (95% CI: -0.99, -0.30) and each SD higher proportion of CD4+CD28-CD57+ cells was associated with a 0.54-year earlier death (95% CI: -0.87, -0.21). Several subsets had significant interactions with sex and race in the fully adjusted model of age at death. A higher proportion of CD4+CD57+ T-cells was significantly associated with lower likelihood of survival to age 90 (relative risk: 0.79) and 1.07-year earlier age at death in males, but not in females. CONCLUSIONS: Our results suggest that CD4+CD57+ cells are associated with earlier death and this relationship was stronger in males than females.
Keywords: Aged; Aged, 80 and over; Aging; Cardiovascular Diseases; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Female; Humans; Killer Cells, Natural; Longevity; Male